Pickering emulsions stabilized by β-CD microcrystals: Construction and interfacial assembly mechanism - Kou, Xingran; Zhang, Xinping; Ke, Qinfei; Meng, Qingran (Frontiers in Nutrition, 2023)
β-Cyclodextrin (β-CD) can combine with oil and other guest molecules to form amphiphilic inclusion complexes (ICs), which can be adsorbed on the oil–water interface to reduce the interfacial tension and stabilize Pickering emulsions. However, the subtle change of β-CD in the process of emulsion preparation is easily ignored. In this study, β-CD and ginger oil (GO) were used to prepare the Pickering emulsion by high-speed shearing homogenization without an exogenous emulsifier. The stability of the emulsion was characterized by microscopic observation, staining analysis, and creaming index (CI). Results showed that the flocculation of the obtained Pickering emulsion was serious, and the surface of the droplets was rough with lamellar particles. In order to elucidate the formation process of the layered particles, the GO/β-CD ICs were further prepared by ball milling method, and the X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), and interfacial tension analyses found that β-CD and GO first formed amphiphilic nanoscale small particles (ICs) through the host–guest interaction, and the formed small particles were further self-assembled into lamellar micron-scale amphiphilic ICs microcrystals. These amphiphilic ICs and microcrystals aggregated at the oil–water interface and finally formed the Pickering emulsion. In this study, by exploring the formation process and evolution of GO/β-CD self-assembly, the formation process and stabilization mechanism of the β-CD-stabilized GO Pickering emulsion were clarified preliminarily, with the aim of providing a theoretical basis for the development of high-performance CD-stabilized Pickering emulsions.